A user-friendly heat-resistant modified polymer-based adhesive for joining and repair of carbon/carbon composites. (5th December 2015) - Wang, Mingchao; Hu, Xiaoxia; Xu, Xiqing; Yun, Ziqi; Liu, Jiachen; Du, Haiyan; Guo, Anran
Abstract: A user-friendly heat-resistant modified polymer-based adhesive was developed to join C/C composites. After calcination at 1300 °C, the bonding effect of the adhesive reached the highest as more heat-resistant ceramics and high-temperature melting glass were generated in the adhesive. Its bonding strength was kept above 15 MPa during test from RT to 500 °C and the corresponding joints ruptured at C/C substrates. Besides, after repeated thermal-cycling at 1300 °C, the bonding strength at this temperature was maintained at about 12 MPa. For cured adhesive without calcination, its bonding strength could be maintained above 5 MPa during the whole heating process, which made it to have direct application in practice after curing. Graphical abstract: Highlights: The bonding effect of adhesive at high temperatures is estimated by high-temperature shear test. The adhesive has excellent heat-resistant property. The practical use is "one-time binding at low temperature without post-processing". The adhesive is used not only for preparing complex components but also for repairing broken parts.